An econometric model of the world cobalt industry - Poonam Gupta (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
This study presents an econometric model of the world cobalt industry, relatively disaggregated to incorporate different demand equations for the United States, and rest of the non-communist world, as well as a breakdown into types of cobalt used. Largely due to reasons of data availability, the model is an annual one and the breakdown by end use categories has been restricted to the United States. Particular attention in the model construction has been given to price setting in the cobalt market. Existing evidence by Burrows (1971) and Charles River Associates (1976) suggests that Zaire sets the price so as to maximise its own profits. The aim of this study is to estimate aggregate and disaggregate short run and long run elasticities with respect to price and activity variables, and to test whether the own profit maximization hypotheses is representative of current producer price setting behaviour when Zaire's share in total world mine production has fallen from nearly two thirds to less than half between 1972 and 1978. Finally, the model constructed is used to simulate the effect of marginal cost pricing by major producers and the movements in price resulting from an exogeneous increase in supply. The latter exercise was motivated by the possibility of a substantial long run source of supply of cobalt from seabed mining.
Keywords: 330